Stunting Incidence in Toddlers Aged 24-59 Months in Kuburaya District Viewed from Feeding Patterns - Dany Permana; Sapja Anantanyu; Aditya Nanda Priyatama (Global Health Science Group, 2023)
Stunting is growth failure in toddlers due to chronic malnutrition and causes children to become short. Stunting is often known as stunting, a state of growth failure in toddlers as indicated by a height-for-age figure of less than -2 (z-score value). Stunting is caused by many aspects, including parenting and nutrition-related eating. The mother's parenting style will determine the toddler's nutritional status. The better the parenting style, the better the nutritional status. The prevalence of stunting in toddlers aged 24-59 years in Kuburaya District is 40.3%. This study aimed to determine the profile of stunting in toddlers aged 24-59 months from the perspective of parenting in Kuburaya District. This research is observational with a random case-control design. Data collection was taken in February-March 2023. The number of case samples was 62 mothers with stunted toddlers, and a control sample of 62 mothers with normal nutritional status toddlers. The data collection technique used a parenting eating pattern questionnaire with height and weight measurements. Data analysis techniques using descriptive statistics. The results revealed that stunting in poor parenting was 85.5% while stunting in good parenting was 14.5% in Kuburaya District. The conclusion from this research is that parenting is related to the incidence of stunting in toddlers, so it is necessary to pay attention to the role of the family, especially mothers, to provide good parenting patterns to prevent stunting.